2001
DOI: 10.1177/088572880102400205
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Attainment of Transition-Related Goals Among Low-income Ethnic Minority Students with Disabilities

Abstract: The Choices-in-Transition Intervention was designed to promote students' attainment of transition-related goals through person-centered goal-setting, help-recruiting skills training, and case management support. Participants were 41 low-income, predominantly ethnic minority high school students with disabilities. The study assessed the types of transitionrelated goals participants set and their goal attainment outcomes. In addition, the study assessed students' help-recruiting skill development, help-seeking b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 25 publications
2
25
0
Order By: Relevance
“…Overall, there is a paucity of research on these experiences and processes, particularly as they relate to urban African American and Latino youth with disabilities (Taylor-Ritzler et al, 2001). Understanding the environmental context that these youth experience is particularly important because they cope with multiple marginalization (e.g., economic and racial discrimination, ableism).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Overall, there is a paucity of research on these experiences and processes, particularly as they relate to urban African American and Latino youth with disabilities (Taylor-Ritzler et al, 2001). Understanding the environmental context that these youth experience is particularly important because they cope with multiple marginalization (e.g., economic and racial discrimination, ableism).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Project Shake-It-Up was developed using a participatory intervention research strategy and a disability studies framework of empowerment to increase self-efficacy and build capacity to set and achieve independent living [8,9] 1 and health promotion goals [3,10,11]. The conceptual basis of the project grew out of related research in the areas of empowerment, capacity building, and participatory methodologies [3,[10][11][12][13][14][15]. Such interventions should include practical skills training for self-advocacy and how to access information and resources.…”
Section: Introductionmentioning
confidence: 99%
“…In a review, McDonald, Balcazar, and Keys (2005) noted that available studies generally have reached favorable conclusions regarding the benefits of mentoring relationships for this population. Authors have specifically reported improvements in participants’ self‐esteem (Buckner, 1993), social competence (Muscott, O’Brien, & College, 1999), academic performance and educational attainment (Buckner, 1993; Moccia, Schumaker, Hazel, Vernon, & Deshler, 1989), classroom conduct and performance (Buckner, 1993; Noll, 1997), employment and job‐training skills (Ryerson‐Espino et al, 2003; Taylor‐Ritzler et al, 2001), and independent living skills (West, Targett, Steininger, & Anglin, 2001). However, as noted by McDonald et al (2005), these investigations have several methodological limitations.…”
mentioning
confidence: 99%